2019
DOI: 10.1186/s13287-019-1146-8
|View full text |Cite
|
Sign up to set email alerts
|

The suppressive effects of miR-508-5p on the odontogenic differentiation of human dental pulp stem cells by targeting glycoprotein non-metastatic melanomal protein B

Abstract: BackgroundAlthough the involvement of glycoprotein non-metastatic melanomal protein B (GPNMB) in regulating the odontogenic differentiation of human dental pulp stem cells (hDPCs) has been identified, the underlying mechanisms are largely unknown. The purpose of this study is to investigate the effects of miR-508-5p on the GPNMB expression and the odontogenic differentiation of hDPCs.MethodsIn this study, hDPCs were isolated and identified by flow cytometric analysis. Based on bioinformatics analysis, dual luc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…In addition, during odontogenesis of DPSCs, miR-508-5p is gradually decreased, while glycoprotein nonmetastatic melanoma protein B (GPNMB), also called osteoactivin, is increased. Further research demonstrated that knockdown of miR-508-5p can promote odontogenesis in DPSCs via upregulation of GPNMB [ 159 ]. In conclusion, miRNAs affect the osteo/odontogenic differentiation of DPSCs by regulating various key molecules in the osteo/odontogenesis process.…”
Section: Epigenetic Mechanisms In Dpscsmentioning
confidence: 99%
“…In addition, during odontogenesis of DPSCs, miR-508-5p is gradually decreased, while glycoprotein nonmetastatic melanoma protein B (GPNMB), also called osteoactivin, is increased. Further research demonstrated that knockdown of miR-508-5p can promote odontogenesis in DPSCs via upregulation of GPNMB [ 159 ]. In conclusion, miRNAs affect the osteo/odontogenic differentiation of DPSCs by regulating various key molecules in the osteo/odontogenesis process.…”
Section: Epigenetic Mechanisms In Dpscsmentioning
confidence: 99%
“…According to reports, Ingenuity® Pathway Analysis results showed that miR-204-5p can directly target ALPL [ 28 ]. Here, the bioinformatics analysis and luciferase reporter experiments further proved that miR-204-5p targets the 3′UTR of the ALPL gene, inhibiting translation of ALPL at the post-transcriptional level.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, multiple indispensable genes related to osteoblasts differentiation and bone mineralization have been revealed. Among these genes, ALPL (alkaline phosphatase) which is recognized as an early expression gene associated with osteogenesis has attracted our attention [ 28 ].. The alkaline phosphatase (ALP) protein it encodes has been widely used as a diagnostic indicator to assess the grade osteoporosis [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, during odontogenesis of hDPSCs, the expression of miR-508-5p decreases gradually, while significant inhibition of odontogenesis is observed after overexpression of miR-508-5p, which targets glycoprotein nonmetastatic melanomal protein B[ 120 ]. Xu et al[ 121 ] reported that during odontoblast differentiation of DPSCs, the expression of miR-21 can be regulated by treating with TNF-α, while downregulation of miR-21 causes a decrease in the expression of dentine matrix protein 1 and DSPP by interacting with STAT3[ 121 ].…”
Section: Multiple Factors Influencing the Odontogenic/osteogenic Differentiation Of Dmscsmentioning
confidence: 99%